Infected Facial Tissue Fillers Caused by Dental Infection - Antoine Berberi; Bouchra Hjeij; Georges Aad; Georges Aoun (Hindawi Limited, 2021)
Injectable dermal fillers are widely used for facial rejuvenation; they help reshape the facial contours by treating volume loss due to aging changes. Facial fillers may become infected following a dental infection. In this report, we present a case of a 44-year-old female patient who presented with a swelling in her upper right buccal region following dental treatment of her second maxillary right premolar. After a thorough history, clinical, and radiological examinations, the diagnosis of infected dermal filler was made. The lesion was treated by association of two antibiotics (ciprofloxacin IM and clindamycin tablets 300 mg), and a complete healing was observed two months after the end of the dental treatments.